PERANCANGAN DAN IMPLEMENTASI SISTEM INFORMASI MANAJEMEN KERJA SAMA PROGRAM STUDI SISTEM DAN TEKNOLOGI INFORMASI UNIVERSITAS MUHAMMADIYAH KOTABUMI - Arafi Fernanda, Aqshal; Jihad Plaza R., M. Abu (JURNAL ILMIAH INFORMATIKA, 2025)
The web-based collaboration information system is designed as an application to facilitate a dynamic and structured collaboration process between Muhammadiyah University of Kotabumi (UMKO) and various external parties. At UMKO, the management of collaboration documents currently faces several significant challenges, including limitations in accessibility and efficiency in handling physical documents. This research aims to address the problems arising from conventional collaboration methods, which are often time-consuming and prone to errors, by offering comprehensive digital solutions to improve overall collaboration effectiveness. The system development method used is the waterfall model, a systematic and structured approach that includes stages such as in-depth needs analysis, detailed system design, careful implementation, rigorous testing, and continuous maintenance. Data collection was carried out through observation of the existing collaboration flow, in-depth interviews with relevant parties such as collaboration units, lecturers, and external partners, as well as comprehensive literature reviews to understand the concepts and best practices in developing collaboration information systems. The research results show that the developed system has successfully and significantly increased the efficiency of collaboration data management, facilitated fast and accurate information access for lecturers, students, and partners, and produced more accurate, comprehensive, and timely collaboration reports. This system is expected to support UMKO in enhancing the quality and quantity of collaborations, expanding its cooperation network, and strengthening the institution's image as a progressive and cooperation-oriented educational institution.